KINERJA BPD DALAM MENGIMPLEMENTASIKAN PERATURAN MENDAGRI NOMOR 110 TAHUN 2016 DI DESA SALARRI KECAMATAN LIMBORO KABUPATEN POLEWALI MANDAR - Ihsan Rizaldy; Sjuaib Hannan; Abdul Khalik (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2021)
The purpose of this study is to find out how BPD'S performance in implementing the Minister of Home Affairs Regulation no. 110 of 2016 in Salarri Village, Limboro District, Polewali Mandar Regency. The study used descriptive methods and data were taken from sources by means of observation, interviews and documentation. The results showed that the BPD still did not understand its duties and functions due to the low education of BPD members so that their performance was also low. The allowance aspect is also low so that the needs of BPD members are not met and their duties are sidelined. The inhibiting factor is the lack of BPD knowledge about its duties and functions. Another factor is the government's lack of firmness in emphasizing the regulations that have been made.